High-temperature magmatic-hydrothermal systems inferred by fumarolic fluids from Callaqui volcano, Biobio region, Chile - Manuel Inostroza; Mauricio Aguilera; Franco Tassi; Maria Clara Lamberti; Felipe Aguilera; Jimena Mailén Presa; Mariano Agusto; Peter H. Barry; Fausto Grassa; Francesco Capecchiacci; Claudia Bucarey; Gabriela Velasquez (Journal of Volcanology and Geothermal Research, 2026)

Depositional facies and mineralogical, geochemical and isotopic features of travertines related to hot springs from Northern Puna, Central Andean Plateau (Argentina) - Yésica Peralta Arnold; M. Gabriela Franco; Pablo J. Caffe; Franco Tassi; Patrocinio Flores; Orlando Vaselli (Journal of South American Earth Sciences, 2026)

Testing sewage sludge and landfill leachate in novel biocovers: A soil column experiment to quantify landfill gas abatement - Gregorio Viti; Stefania Venturi; Antonio Randazzo; Fabio Tatàno; Franco Tassi (Waste Management, 2026)

Temporal evolution of fumarolic gas geochemistry at the Nevados de Chillán Volcanic complex (2013−2023): Signals of volcanic unrest and insights into the hydrothermal system - Daniele Tardani; Marco Taussi; Franco Tassi; Jorge E. Romero; Philippe Robidoux; Camila Poblete-González; Fernanda Álvarez-Amado; Lorenzo Manosalva; Claudia Berrios; Daniele L. Pinti; Martin Reich; Diego Morata; et al. (Journal of Volcanology and Geothermal Research, 2025)

Newly discovered CO2 (carbon dioxide) vent cave drives r-strategy shift in a Mediterranean aphotoendosymbiotic coral - Chiara Cassarino; Arianna Mancuso; Fiorella Prada; Teresa Sani; Silvia Dall'Ara; Oscar Wallnoefer; Chiara Marchini; Franco Tassi; Alessandra Campanelli; Mauro Marini; Jörg U. Hammel; Jaap A. Kaandorp; et al. (Science of The Total Environment, 2025)

Diffuse CO2 and CH4 emissions of two volcanic lakes on Pico Island (Azores) - César Andrade; J. Virgílio Cruz; Letícia Ferreira; Fátima Viveiros; Duarte Toubarro; Franco Tassi; Adriano Pimentel; Diogo Braga; António Cordeiro; Pedro Raposeiro (Journal of Volcanology and Geothermal Research, 2025)

Geochemical survey of thermal springs from the Atacama region, northern Chile - Manuel Inostroza; Yazmin Godoy; María Donoso-Peña; Franco Tassi; Felipe Aguilera; Francesco Capecchiacci; Andrea Luca Rizzo (Journal of Volcanology and Geothermal Research, 2025)

C-based gas (CH4 and CO2) fluxes from eutrophicated volcanic shallow lakes in Corvo Island (Azores, Portugal) - J. Virgílio Cruz; César Andrade; Duarte Toubarro; Letícia Ferreira; Adriano Pimentel; Fátima Viveiros; Franco Tassi; António Cordeiro; Diogo Braga; Pedro Raposeiro (Applied Geochemistry, 2025)

Lithogeomorphological factors for wet meadows formation and sustenance in dryland setting in Domuyo mount, Patagonia, Argentina - Esteban Villalba; Silvina C. Carretero; María F. Lajoinie; Franco Tassi (Journal of South American Earth Sciences, 2025)

Hydrogeochemical processes governing the origin, mobility and transport of trace elements in the Domuyo Volcanic complex Geothermal system (Patagonia, Argentina) - Joaquin Llano; Lorenza Li Vigni; Mariano Agusto; Lorenzo Brusca; Alberto Caselli; Giovanni Chiodini; Walter D'Alessandro; Matteo Lelli; Franco Tassi; Orlando Vaselli; Sergio Calabrese (Journal of Volcanology and Geothermal Research, 2025)

Relationship of magmatic fluids to high-enthalpy geothermal systems: New insights from the Tolhuaca Geothermal System (TGS), Southern Andes - Philippe Robidoux; Daniele Tardani; Pablo Sánchez-Alfaro; Marco Liuzzo; Diego Morata; Yves Moussallam; Estelle F. Rose-Koga; Franco Tassi; Pamela Pérez-Flores; Fausto Grassa; Vincenzo Francofonte (Chemical Geology, 2025)

Monitoring air pollutants in urbanized hydrothermal areas: challenges and benefits of traditional measurement strategies - Leonardo Fantini; Stefania Venturi; Francesco Capecchiacci; Tullio Ricci; Rebecca Biagi; Franco Tassi (Environmental Geochemistry and Health, 2025)
Carbon- and sulfur-bearing gases are emitted at relevant amounts from hydrothermal manifestations at Tivoli Terme (Latium, central Italy), where different potential anthropogenic contaminant sources also occur. This study presents a geochemical dataset including CO 2 , CH 4 , SO 2, and H 2 S concentrations and δ 13 C-CO 2 and δ 13 C-CH 4 values measured in air at the center of Tivoli town. The main aim was to evaluate the impact on air quality of hydrothermal manifestations and anthropogenic activities employing a traditional stationary monitoring strategy. The analytical results reveal significant air contamination from both natural and anthropogenic emissions, although gas levels were below outdoor air quality thresholds. Carbon dioxide and CH 4 were primarily linked to anthropogenic sources, while hydrothermal emissions played a secondary role. However, H 2 S concentrations up to 282 ppb highlighted a notable impact from hydrothermal emissions surrounding the measurement station, where SO 4 -rich pools are located. Nevertheless, the geochemical data did not provide a reliable estimate of the specific contributions from each source. The study identifies key limitations in relying on a single fixed monitoring station, as weather conditions highly influence it and cannot reliably capture the relative impacts of various sources across a broad area. Additionally, compositional and isotopic geochemical parameters often produce ambiguous results, complicating the differentiation of pollution sources. An integrated approach is recommended, combining mobile stations for periodic pollutant mapping with low-cost instruments deployed at strategic locations near potential sources and progressively farther away. This strategy could better track the spatial and temporal evolution of contaminant concentrations, addressing the shortcomings of current monitoring systems and enhancing mitigation efforts.

Unusual boron isotopic value and hydrochemical characteristics of thermal springs indicating magmatic fluids upwelling along Cuona-Sangri rift in the Tibet (China) - Peixin Cong; Hongbing Tan; Zhiwei Shi; Fei Xue; Franco Tassi; Yulong Li (Geothermics, 2025)

The 2021–2023 unrest of Vulcano Island volcanic system (Aeolian Islands, Italy): geochemical evidence from fumarolic gas discharges and well waters - Francesco Capecchiacci; Franco Tassi; Orlando Vaselli; Stefania Venturi (Bulletin of Volcanology, 2025)

Trace element transport by volcanic gases at Vulcano (Sicily, Italy) – Speciation, deposition and fluxes - Celine L. Mandon; Hanna Kaasalainen; Sergio Calabrese; Everett L. Shock; Panjai Prapaipong; Franco Tassi; Ingvi Gunnarsson; Jóhann Gunnarsson-Robin; Andri Stefánsson (Journal of Volcanology and Geothermal Research, 2025)

Biogeochemical and microbial community structure differently modulates CO2 and CH4 dynamics in two adjacent volcanic lakes (Monticchio, Italy) - Stefano Fazi; Jacopo Cabassi; Francesco Capecchiacci; Cristiana Callieri; Ester M Eckert; Stefano Amalfitano; Luca Pasquini; Roberto Bertoni; Orlando Vaselli; Franco Tassi; Bertram Boehrer; Giovannella Pecoraino; et al. (Ecohydrology & Hydrobiology, 2025)

Geochemical and isotopic characterization of the shallow aquifers from the Mugello Basin (Tuscany, central Italy): Implications for assessing a monitoring network in a seismically active area - Lorenzo Chemeri; Jacopo Cabassi; Franco Tassi; Francesco Capecchiacci; Andrea L. Rizzo; Stefano Caliro; Orlando Vaselli (Journal of Geochemical Exploration, 2024)

Quantification of volcanic degassing and analysis of uncertainties using numerical modeling: the case of Stephanos crater (Nisyros Island, Greece) - Silvia Massaro; Giancarlo Tamburello; Giulio Bini; Antonio Costa; Manuel Stocchi; Franco Tassi; Rebecca Biagi; Orlando Vaselli; Giovanni Chiodini; Fabio Dioguardi; Jacopo Selva; Laura Sandri; et al. (Bulletin of Volcanology, 2024)
Nisyros Island (Greece) is affected by widespread gas emissions from fumarolic fields located at the bottom of hydrothermal craters in the southern part of its caldera. This morphology and the current low gas fluxes make Nisyros an ideal site for testing the limits of physics-based gas dispersal models in confined and low-emission conditions. Here, we focused our attention on the local scale volcanic gas dispersion from the Stephanos hydrothermal crater. In April 2023, a 1-week survey was carried out to measure weather data, CO 2 and H 2 S gas fluxes, air concentrations from portable gas stations, and chemical composition of fumarolic gases and to acquire thermal images of the crater floor. These data were used as inputs and boundary conditions for numerical simulations using a DISGAS-2.6.0 model in order to quantify the present-day volcanic degassing and its associated uncertainties, accounting for the meteorological variability. Model results are provided in terms of H 2 S probabilistic exceedance and persistence maps, showing gas concentrations within the crater that fall below the thresholds indicated for the occurrence of serious respiratory problems. Since DISGAS-2.6.0 does not account for chemical reactions, this study represents a good opportunity to discuss the methodological limits of simulating the dispersion of H 2 S which is challenging due to its rapid degradation and dilution in the atmosphere. In this regard, we also provided an empirical law of the H 2 S depletion in low-emission conditions that takes into account the uncertainties related to the field measurements.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Identifying potential uses for green roof discharge based on its physical–chemical-microbiological quality - Jonas Onis Pessoa; Daniel Gustavo Allasia Piccilli; Cristiano Gabriel Persch; Rutineia Tassi; Jordana Georgin; Dison S. P. Franco; Yamil L. de O. Salomón (Environmental Science and Pollution Research, 2024)

Volatile organic compounds (VOCs) from diffuse degassing areas: Interstitial soil gases as message bearers from deep hydrothermal reservoirs - Stefania Venturi; Antonio Randazzo; Jacopo Cabassi; Daniele Cinti; Federica Meloni; Monia Procesi; Barbara Nisi; Nunzia Voltattorni; Francesco Capecchiacci; Tullio Ricci; Orlando Vaselli; Franco Tassi (Science of The Total Environment, 2024)

Evidence of “Lake Nyos-type” behavior in the geological record: A review - Amin Nsangou Mouhamed; Dmitri Rouwet; Franco Tassi; Wilson Yetoh Fantong; Oumar Farouk Mouncherou; Emile Ekomane; Nathalie Fagel (Earth-Science Reviews, 2023)

Geochemistry of thermal springs and associated gases along the Strymon River Valley (Bulgaria and Greece) - Angelo Minissale; Orlando Vaselli; Peter Marchev; Franco Tassi (Journal of Geochemical Exploration, 2023)

A conceptual model for the Tufiño-Chiles-Cerro Negro (TCCN) geothermal system (Ecuador-Colombia): New insights into geothermal exploration from chemical and isotopic composition of hydrothermal fluids - Marco Taussi; Daniele Tardani; Franco Tassi; Andrea Gorini; Eduardo Aguilera; Bruno Capaccioni; Alberto Renzulli (Journal of Geochemical Exploration, 2023)

Degradation of biogas in a simulated landfill cover soil at laboratory scale: Compositional changes of main components and volatile organic compounds - Antonio Randazzo; Francesca Zorzi; Stefania Venturi; Gabriele Bicocchi; Gregorio Viti; Fabio Tatàno; Franco Tassi (Waste Management, 2023)

Small-magnitude earthquakes triggering fluid vents in a pressurised CO2 system, Caprese Michelangelo (Central Italy) - Marco Bonini; Gabriele Bicocchi; Domenico Montanari; Giovanni Ruggieri; Franco Tassi; Francesco Capecchiacci; Orlando Vaselli; Federico Sani; Daniele Maestrelli (Tectonophysics, 2023)

Sources and migration pathways of methane and light hydrocarbons in the subsurface of the Southern Po River Basin (Northern Italy) - Andrea Ricci; Stefano Cremonini; Paolo Severi; Franco Tassi; Orlando Vaselli; Andrea Luca Rizzo; Antonio Caracausi; Fausto Grassa; Jens Fiebig; Bruno Capaccioni (Marine and Petroleum Geology, 2023)

Insights into the Porretta Terme (northern Apennines, Italy) hydrothermal system revealed by geochemical data on presently discharging thermal waters and paleofluids - Franco Tassi; Paolo S. Garofalo; Filippo Turchetti; Davide De Santis; Francesco Capecchiacci; Orlando Vaselli; Jacopo Cabassi; Stefania Venturi; Stefano Vannini (Environmental Geochemistry and Health, 2022)
This study focuses on the geochemical features of the presently discharging thermal and cold springs and on paleofluids from the upstream portion of the Reno river basin (Alto Reno; central–northern Italy). The aim is investigating the primary sources of the modern and fossil fluids and the interactions between deep and shallow aquifers. Paleofluids are from fluid inclusions hosted within euhedral and hopper quartz crystals and consist of a two-phase, liquid–vapor aqueous fluid and a unary CH 4 fluid. The aqueous inclusions have constant phase ratios and a calculated salinity of ~ 1.5 wt% NaCleq. They homogenize by bubble disappearance at 100–200 °C, whereas the estimated entrapment depth is ~ 3–5.5 km. The paleofluids likely represent the vestiges of the deep and hot, CH 4 -rich, Na + –Cl − fluids produced by the interaction between meteoric waters and Triassic and Miocene formations. The modern Na + –Cl − (HCO 3 − ) thermal waters originate from meteoric waters infiltrating SW of the study area, at elevation > 800 m a.s.l., circulating within both the Triassic evaporites and the overlying Miocene turbiditic formations, where salt dissolution/precipitation, sulfate reduction, and production of thermogenic CH 4 occur. The equilibrium temperature of the deep fluid source is ~ 170 °C, corresponding to > 5 km depth. Cold springs are Ca 2+ –HCO 3 − type and show low amounts of biogenic CO 2 and CH 4 with no inputs of deep-originated fluids excepting in the immediate surroundings of the thermal area, confirming the lack of significant hydraulic connection between shallow and deep aquifers. We propose a genetic link between the quartz-hosted paleofluid and the thermal waters present in the area.

Geochemistry of fluids discharged from mud volcanoes in SE Caspian Sea (Gorgan Plain, Iran) - Mahin Farhadian Babadi; Behzad Mehrabi; Franco Tassi; Jacopo Cabassi; Elena Pecchioni; Ata Shakeri; Orlando Vaselli (International Geology Review, 2021)

Geochemistry of gas and water discharge from the magmatic-hydrothermal system of Guallatiri volcano, northern Chile - Manuel Inostroza; Franco Tassi; Felipe Aguilera; José Pablo Sepúlveda; Francesco Capecchiacci; Stefania Venturi; Giorgio Capasso (Bulletin of Volcanology, 2020)

Active hydrothermal fluids circulation triggering small-scale collapse events: the case of the 2001–2002 fissure in the Lakki Plain (Nisyros Island, Aegean Sea, Greece) - Stefania Venturi; Franco Tassi; Orlando Vaselli; Georges E. Vougioukalakis; Heba Rashed; Christos Kanellopoulos; Chiara Caponi; Francesco Capecchiacci; Jacopo Cabassi; Andrea Ricci; Luciano Giannini (Natural Hazards, 2018)

Origin of fumarolic fluids from Tupungatito Volcano (Central Chile): interplay between magmatic, hydrothermal, and shallow meteoric sources - Oscar Benavente; Franco Tassi; Francisco Gutiérrez; Orlando Vaselli; Felipe Aguilera; Martin Reich (Bulletin of Volcanology, 2013)

Biogeochemical processes involving dissolved CO2 and CH4 at Albano, Averno, and Monticchio meromictic volcanic lakes (Central–Southern Italy) - Jacopo Cabassi; Franco Tassi; Orlando Vaselli; Jens Fiebig; Matteo Nocentini; Francesco Capecchiacci; Dmitri Rouwet; Gabriele Bicocchi (Bulletin of Volcanology, 2013)

Evolution of fluid geochemistry at the Turrialba volcano (Costa Rica) from 1998 to 2008 - O. Vaselli; Franco Tassi; E. Duarte; E. Fernandez; R. J. Poreda; A. Delgado Huertas (Bulletin of Volcanology, 2010)